Gestión administrativa en la Cooperativa de Taxis San Fernando de la Ciudad de Babahoyo - Nuñez Montero, Mabel Carolina (2020)
The case study was carried out at the San Fernando Taxis Cooperative in the city of Babahoyo, an institution dedicated to providing transportation services from one place to another, according to the needs or requirements of the general population. The purpose of the research is to analyze the administrative management of the cooperative since over the years it has faced serious problems in its planning, management and administration of resources that have prevented it from meeting the planned objectives, since its administrative processes are inadequate due to the lack of coordination between areas, poor communication between partners and the administrative department. The applied methodology is descriptive and documentary because it allowed to interpret and analyze information from the identified events and support this documentation; The inductive method was also used, which helped to determine subproblems related to administrative management, together with the techniques of direct observation of the transport units and surveys directed at the administration and members of the cooperative through the execution of investigative instruments such as observation and question questionnaire. The results obtained from the investigative process are: problems in coordinating the activities to be developed by the administrative members, the lack of organizational tools and management indicators to evaluate the performance of employees and the optimal state of their vehicle units and the lack of a manual of functions that establishes the responsibilities and obligations of the members of the organization.